2018
DOI: 10.1159/000488483
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Potassium and Mild Cognitive Impairment in Mexican-Americans

Abstract: Background: Recent evidence suggests that increasing dietary intake of minerals reduces the risk of dementia. This study aimed to examine the relationship between potassium and diagnosis of mild cognitive impairment (MCI) in a sample of older Mexican-Americans from rural and urban populations. Methods: The sample was formed of a total of 139 participants with MCI and 371 normal controls from two independent cohorts: a rural cohort (Facing Rural Obstacles to Healthcare Now through Intervention, Education and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…These findings contradict our premise of lower potassium levels www.kjcls.org that are related to MCI status. A plausible explanation may be the different socioeconomic status and biological components in our population [24].…”
Section: Discussionmentioning
confidence: 93%
“…These findings contradict our premise of lower potassium levels www.kjcls.org that are related to MCI status. A plausible explanation may be the different socioeconomic status and biological components in our population [24].…”
Section: Discussionmentioning
confidence: 93%
“…Previous research has also found that high serum potassium levels were associated with mild cognitive impairment (Vintimilla et al, 2018), while high glucose levels were associated with low gray matter density and FA (Weinstein et al, 2015). Higher GT levels, as an index of liver function, has previously been associated with brain volume shrinkage in patients with alcohol dependence (Chen et al, 2012), brain infarcts in a healthy population (Nam et al, 2019), and cardiovascular mortality (Ruttmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of acute cognitive deficits, the dysphagia clinician should consider the patient's prior level of cognitive function and the likelihood that the cognitive function will return after the acute event is resolved. For example, individuals with acute electrolyte abnormalities may have acute cognitive deficits that are likely to resolve once the electrolyte balance is restored (Vintimilla et al, 2018). The dysphagia clinician must determine a patient's safety and available support during this period of altered cognition and attend to the impact on daily eating and oral care routines.…”
Section: General Healthmentioning
confidence: 99%